The effect of K-line classification in different cervical dynamic position on surgical outcomes in patients with ossification of the posterior longitudinal ligament after anterior controllable antedisplacement and fusion - Han, Lin-Hui; Sun, Kai-Qiang; Yan, Chen; Sun, Jing-Chuan; Shi, Jian-Gang (Frontiers in Surgery, 2022)
Abstract Purpose: To investigate whether the K-line classification in different cervical dynamic position of patients with Ossification of the Posterior Longitudinal Ligament (OPLL) affects clinical outcome after Anterior Controllable Antedisplacement and Fusion (ACAF) surgery. Methods: A total of 93 patients who suffered from cervical spondylosis caused by OPLL underwent ACAF surgery between June 2015 and December 2017 in a single institution. Neutral, neck-flexed and neck-extended cervical radiographs were obtained from every patient. Subsequently they were classified into K-line (+) and K-line (-) with reference to the K-line classification criteria. Clinical outcomes were assessed by the JOA score, improvement rate (IR) and visual analogue scale (VAS). Radiological assessment included Cobb angle and occupation ratio (OR) of OPLL. Correlations between the long-term surgical outcomes and classification of K-line in different dynamic position were analyzed by one-way analysis of variance. Results: Significant improvements were shown in all postoperative clinical and radiographic assessments (P ＜ 0.05). There were no differences in IR, Cobb angle and VAS among flexion K-line (-), flexion K-line (+), extension K-line (-) and extension K-line (+) at the two-year follow-up (P ＞ 0.05). However, the OR of extension K-line (-) (16.13% ± 11.58%) was higher than that of extension K-line (+) (9.00% ± 10.27%) and flexion K-line (+) subgroup (9.47% ± 9.97%) (P＜0.05). Conclusion: The ACAF procedure has shown satisfactory surgical outcomes in various K-line classifications in different dynamic position.